Bild und Betrachter : auf der Suche nach Eindeutigkeit - Kebeck, Günther (Regensburg : Verlag Schnell & Steiner Regensburg, 2006)
Magritte, René ; Cézanne, Paul ; Pistoletto, Michelangelo ; Picasso, Pablo ; Monet, Claude ; Hopper, Edward ; De Chirico, Giorgio ; Morandi, Giorgio ; Albers, Josef ; Seurat, Georges ; Mondriaan, Piet ; Rothko, Mark ; Newman, Barnett ; Tobey, Mark ; Dali, Salvador ; Piranesi, Giovanni Battista ; Wols ; Dierickx, Karel ; Giacometti, Alberto ; Twombly, Cy ; Morellet, François
Bibliog. p. 328-334
Glossarium p. 322-327
Duits
boek